Comparison of field population growths of three cereal aphid species on winter wheat - Vojtěch Jarošík; Alois Honěk; A. Tichopád (Plant Protection Science, 2003)
Population growths of three aphid species colonising winter wheat stands, Metopolophium dirhodum, Rhopalosiphum padi and Sitobion avenae, were analysed by regression method. The calculations were based on counts in 268 winter wheat plots at 3 or 7 day intervals over 10 (leaves) or 6 (ears) years. The population dynamics of a particular species differed widely between years. Density independent exponential growth of the population was most common, but its rate differed significantly between species, and for S. avenae also between populations on leaves and ears, on which the populations grew fastest. Field estimates of the intrinsic rate of increase derived from the exponential growths ranged between 0.010-0.026 in M. dirhodum, 0.0071-0.011 in R. padi, and between 0.00078-0.0061 and 0.0015-0.13 in S. avenae on leaves and ears, respectively. In the populations with the most vigorous population growth, S. avenae on ears and M. dirhodum on leaves, the rate of population increase significantly decreased with increasing aphid density.